1999
DOI: 10.1136/emj.16.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Chickenpox pneumonia: case report and literature review.

Abstract: The incidence of primary chickenpox infection in young adults appears to be rising in the UK and other developed countries. The infection is more severe in adults than in children and complications, including pneumonia, are more frequent. An illustrative case of severe chickenpox pneumonia in an immunocompetent, non-pregnant adult smoker is presented. The epidemiology and pathology of the disease is discussed and a review of current management in the emergency department and the intensive care unit is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
17

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
0
9
0
17
Order By: Relevance
“…6,7 As for VZV pneumonia, antiviral therapy including intravenous acyclovir 10-15 mg/kg every 8 hourly for 7-10 days was initiated in 66 out of 120 patients. [26][27][28][29][30][31][32][33][34][35][36][37][38] Two patients were treated with vidarabine before the widespread use of acyclovir. 27,38 Corticosteroids were combined with acyclovir in 17 patients.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 As for VZV pneumonia, antiviral therapy including intravenous acyclovir 10-15 mg/kg every 8 hourly for 7-10 days was initiated in 66 out of 120 patients. [26][27][28][29][30][31][32][33][34][35][36][37][38] Two patients were treated with vidarabine before the widespread use of acyclovir. 27,38 Corticosteroids were combined with acyclovir in 17 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Suggested dosage is 10-15mg/kg 3 times daily for 7 days. Some authors reported good response to corticosteriods, while others considere them contraindicated in pregnancy (6) .…”
Section: Discussionmentioning
confidence: 99%
“…10 Fine crackles are typically found on respiratory examination, especially in the lower lung fields. 12 However, the respiratory examination can be normal, and the absence of signs does not indicate low risk disease. 13 In the acute setting, chest radiography typically shows nodular or interstitial pneumonitis, often with apical sparing.…”
Section: Long Answermentioning
confidence: 99%
“…2 The chest radiograph should also be inspected for consolidation (which may reflect bacterial infection or a congregation of varicella related nodules), pleural effusions, and hilar adenopathy, all of which can be features of varicella pneumonitis. 12 The differential diagnosis of widespread small nodules on chest radiography includes miliary tuberculosis, neoplastic metastases, sarcoidosis, pneumoconiosis, and fungal infection. The differential diagnosis of a vesicular rash includes drug related eruptions, contact dermatitis, erythema multiforme, enteroviral infections (hand, foot, and mouth disease; with characteristic peripheral distributions of white-grey flat vesicles), impetigo, disseminated molluscum contagiosum, scabies, and pityriasis rosea.…”
Section: Long Answermentioning
confidence: 99%